The Sand of Caparica : A history of human intervention in a beach-dune system (Portugal) - Palma, Monique (2021)
A historical research about the human intervention in Costa da Caparica, particularly at S. João beach, starting in the 19th century, with the first dunes’ survey, the afforestation experiences and the construction of a drainage system. A long-term perspective on the socio-evolution of these hybrid environments.